Application issues of compulsory conciliation in the settlement of fishery disputes in the Yellow Sea - Pan, Xiaolin (Frontiers in Marine Science, 2023)
China and South Korea have made great efforts to settle their fishery disputes in the Yellow Sea through political negotiations. The results of the bilateral treaty, which was concluded around 2001, have been very limited. The Law of the Sea’s compulsory conciliation procedure can become an alternative choice for two countries to settle fishery disputes. This article starts with a comparative study of fishery disputes in the Yellow Sea that should be subject to compulsory conciliation. Based on the similarities among these disputes, it is argued that compulsory conciliation is applicable to the settlement of fishery disputes in the Yellow Sea. This article also pays attention to some essential issues related to the application of compulsory conciliation, including the jurisdiction and powers of the Conciliation Commission and the implementation of the report concluded by the Conciliation Commission.